2019
DOI: 10.1037/adb0000522
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol administration reduces attentional bias to alcohol-related but not food-related cues: Evidence for a satiety hypothesis.

Abstract: Attentional bias to alcohol is a well-documented effect whereby drinkers allocate greater visual attention toward alcohol-related stimuli rather than nonappetitive, neutral stimuli. Some recent research has shown that acute administration of alcohol temporarily reduces attentional bias to alcohol cues, possibly because alcohol consumption satiates the motivation to drink. However, the specificity of this effect has not been tested, and so it is unclear whether reduced attentional bias following alcohol is spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
15
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 36 publications
4
15
1
Order By: Relevance
“…This is consistent with the 'satiation hypothesis' suggesting that the absence of 'reward' satiation in striatum activates hypervigilance for alcohol-related stimuli, in an attempt to attain satiety (Monem and Fillmore, 2019). Specifically, findings by Monem and Fillmore (2019) indicate that AB for alcohol-related stimuli shows dose-dependent decreases; however, the same pattern of decreases was not observed for other appetitive stimuli. These findings are also consistent with those suggestive of elevated AB following placebo (McNeill et al, 2021).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…This is consistent with the 'satiation hypothesis' suggesting that the absence of 'reward' satiation in striatum activates hypervigilance for alcohol-related stimuli, in an attempt to attain satiety (Monem and Fillmore, 2019). Specifically, findings by Monem and Fillmore (2019) indicate that AB for alcohol-related stimuli shows dose-dependent decreases; however, the same pattern of decreases was not observed for other appetitive stimuli. These findings are also consistent with those suggestive of elevated AB following placebo (McNeill et al, 2021).…”
Section: Discussionsupporting
confidence: 86%
“…Specifically, anticipation was associated with significant increases in alcoholrelated attentional bias. This is consistent with the 'satiation hypothesis' suggesting that the absence of 'reward' satiation in striatum activates hypervigilance for alcohol-related stimuli, in an attempt to attain satiety (Monem & Fillmore, 2019). Specifically, findings by Monem and colleagues indicate that attentional bias for alcohol-related stimuli show dose-dependent decreases; however, the same pattern of decreases was not observed for other appetitive stimuli (ibid).…”
Section: Discussionsupporting
confidence: 83%
“…This posits that the transient reductions in AB following alcohol intoxication detected in the pre-load condition, are the result of alcohol's rewarding effects satiating one's motivations to consume and by extension attentional allocation to alcohol-related stimuli (i.e., Duka & Townshend, 2004;Weafer & Fillmore, 2013). Further support comes from recent findings that indicate that AB for alcohol-related stimuli but not food stimuli is reduced following acute alcohol intoxication (Monem & Fillmore, 2019). On the 20 other hand, the placebo condition would be expected to elicit anticipatory effects (see Marlatt, Demming, & Reid, 1973) without the associated dampening effects of satiation on AB, as might be expected as a result of intoxication.…”
Section: Discussionmentioning
confidence: 95%
“…Gough et al [ 66 ] observed that AB to food cues increased following a higher dose alcohol primer (0.6 mg/kg) compared to placebo, suggesting that these effects may only occur at higher doses. A smaller study in 23 young adults found that while low- (0.3 g/kg) and high-dose (0.65 g/kg) alcohol primers reduced alcohol-cue related AB relative to placebo, AB towards food-cues were sustained across all doses [ 69 ]. Recent evidence has indicated that alcohol (beer) odour increased attentional bias for food-cues, even in the absence of actual alcohol consumption [ 70 ].…”
Section: Resultsmentioning
confidence: 99%